The effect of a sprint training program upon fructose 1,6-diphosphatase activity in the soleus and the white portion of the vastus lateralis of the rat - Beauregard, Marie (University of Ottawa (Canada), 1976)
Abstract not available.
Keywords: Health Sciences, Recreation.; Biology, Physiology.